Effects of temperature, sestonic algae features, and seston mineral content on cladocerans of a tropical lake - Fileto, Claudia [UNESP]; Arcifa, Marlene Sofia; Henry, Raoul [UNESP]; Ferreira, Rosa A. R. [UNESP] (Edp Sciences S A, 2010)
The effects of temperature on the life table, and of seston quality on the individual growth and reproduction of cladocerans from a tropical lake were tested in the laboratory. Life-table experiments were carried out at 17 degrees C, 23 degrees C, and 27 degrees C. Growth bioassays tested the influence of natural seston fractions, separated by net filtration, on cladocerans. The treatments were: (1) total seston plus Scenedesmus spinosus (1 mg C.L(-1)), (2) seston <= 36 mu m, and (3) seston >36 mu m. Phytoplankton composition, density, and biomass were evaluated during growth experiments, together with sestonic carbon, nitrogen, and phosphorus concentrations. The intrinsic rates of natural increase were higher for Moina micrura and Daphnia ambigua at 27 degrees C compared to 17 degrees C. The age at first reproduction of both species was delayed at 17 degrees C. Growth rates and fecundity of M. micrura were higher in the seston fraction <= 36 mu m than in the fraction > 36 mu m. Higher growth rates and fecundity of Moina minuta were observed in the seston enriched with the green alga in comparison to the seston <= 36 mu m and > 36 mu m. Bosmina longirostris was unable to reproduce at 17 degrees C and to grow in the seston > 36 mu m in one experiment. High densities and/or biomass of large colonial and filamentous algae present in the larger seston fraction could have contributed to reduce growth and reproduction. Episodes of food-quantity limitation may occur, but there was no evidence of mineral limitation, although seston C:P and C:N ratios were always above the limiting values assumed for temperate water bodies. The C:P and C:N ratios arc highly influenced by carbon that originates primarily from resuspended detritus from the lake.
Keywords: Food size; nitrogen; phosphorus; seston; temperature; tropical cladocerans